Enhancing Social Impacts of Third Sector Organizations Amid the Covid-19 Pandemic - Raptopoulos, M. M. S. C.; Simaens, A. (16th European Conference on Innovation and Entrepreneurship, 2021)
The effectiveness achieved by Third Sector Organizations (TSOs) is directly linked to goals based on their missions and results generated by their actions, which can positively or negatively impact their beneficiaries. Even in normal situations, there is already a difficulty in gathering resources to maintain their operations. The advent of the Covid-19 pandemic tends to worsen this situation depending on their social innovation and resilience capacities. From such an issue, the present study identifies strategies and lessons learned by Portuguese and Brazilian TSOs that were affected by the Covid-19 pandemic. Moreover, an assessment is made on what they did to maximize the positive social impacts and minimize the negative ones, considering the crisis management theory. Then, a qualitative phenomenological-type exploratory research was conducted, whose data was collected primarily from in-depth interviews and secondarily from documents published in the TSOs’ websites. The data collected from thirty-two Portuguese and Brazilian TSOs were assessed by means of content analysis, based on existing theory and on new subjects arisen from the reported experiences. The results have shown that, regardless the institutional model, most of them were not prepared to deal with that crisis. Besides, they had been reacting as the effects were underway, seeking to maximize the positive social impacts and to minimize the negative ones. Additionally, it is highlighted the importance of a flexible management to adapting to a new challenge in order to achieve different priority goals and to meet the main beneficiaries’ needs during the pandemic. Although in an early-stage research, interesting results have already been found, which can lead to contributions to management, governance, leadership, strategy, social innovation, sustainability and, ultimately, to the design of a crisis management model for TSOs. This research also calls for complementary future works.